Pengaturan Hukum Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK) Sebagai FIU (Financial Inteligence Unit) di Indonesia - BR, Wahyudi (LPPM Universitas Ekasakti Padang, 2024)
Establishment of the Financial Transaction Reports and Analysis Center (PPATK) in order to prevent and eradicate money laundering crimes in Indonesia. PPATK is an independent institution which in carrying out its duties and authority is directly responsible to the President. In this case, PPATK carries out an analysis of reports received from Financial Service Providers or other parties. Based on the results of the analysis, if indications of a criminal act of money laundering are found, the results of the analysis are submitted to law enforcement officials as financial intelligence information for follow-up. PPATK also plays a role in assisting law enforcers in dealing with other criminal acts by using various information they have or the results of analyzes carried out. PPATK has the task of preventing and eradicating the crime of money laundering. In an effort to effectively prevent and eradicate the crime of money laundering, the government has played a real role and has a high commitment, including by handling the crime of money laundering in Indonesia since the enactment of Law Number 15 of 2002 concerning the Crime of Money Laundering as amended by Law. - RI Law Number 25 of 2003 concerning amendments to Republic of Indonesia Law Number 15 of 2002 concerning the Crime of Money Laundering. Even though these two laws have shown a positive direction, they are not yet optimal. For this reason, Republic of Indonesia Law Number 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering (UU TPPU) was formed.